DAMPAK PENGEMBANGAN KEBUN KOMUNITAS TERHADAP PRODUKTIVITAS PANEN, DIGITALISASI TRANSAKSI, DAN PENGELOLAAN LIMBAH: PKM SAUNG ASRI 2 DI JAKARTA UTARA - Suciati Permata; Asri Ardiati Sunoto; Septiani Juniarti (Universitas Mataram, 2026)
This community service program was carried out at Saung Asri 2 Garden, RT.001 RW.003, Tugu Selatan, North Jakarta. The area, previously an underutilized negative space, was transformed into a productive green area through local community initiatives. The program aimed to empower the community by enhancing urban farming productivity, business management, and the use of appropriate technology. The methods included socialization, training, technology implementation (hydroponics, drip irrigation, composting, QRIS), mentoring, and participatory evaluation. The results showed improved harvest productivity, diversification of processed products (spinach chips, hydroponic vegetables), and strengthened community institutions. Active community participation was evident in garden management, digital payment use, and organic waste composting. The garden also became an educational and social space, supporting the achievement of Sustainable Development Goals (SDGs) 2, 8, 11, and 12. In conclusion, the development of Saung Asri 2 Garden has made a tangible contribution to improving the community’s economic, social, and environmental well-being.